A Study of Egg Quality, Fertility and Hatchability in Kashmiri Rhode Island Red Chicken Breed - Beenish Shahid,; Maira Ihsan,; Muhammad Ijaz Khan, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The fertility and hatchability of the eggs are traits of economic importance in poultry production. The Kashmiri Rhode Island Red (RIR) breed maintained under an intensive management system by the Government Poultry Farm Chacksagher, Mirpur, was assessed to study productive performance. The birds were provided with a standard formulated chick mash throughout the brooding period, grower ration for an additional period and layers mash from 21 weeks onwards. The results revealed that up to week 40, Kashmiri RIR males and females had an average weight of 2.74 ± 0.05 kg and 2.02 ± 0.04 kg, respectively. The mean age at sexual maturity was found to be 148 ± 1.22 days. The overall egg production percentage was 72.21 ± 2.40 with mean egg weight 52.94 g, shape index 77.90%, shell weight 4.94 g, shell thickness 0.30 mm, albumen weight 28.88 g, and yolk weight 16.26 g. The albumen and yolk height were 6.51 and 16.26 mm, respectively. The fertility was 88.60% while hatchability was 93.48% based on fertile eggs. Significant positive correlations were observed between age/fertility (0.712), age/hatchability of fertile eggs (0.561), age/hatchability of all eggs (0.681), fertility/hatchability of fertile eggs (0.857), fertility/hatchability of all eggs (0.982) hatchability of fertile eggs/hatchability of all eggs (0.938). In contrast significant negative correlations were assessed between traits like age/dead in germ (-0.748), shape index/dead in shell (-0.798), dead in germ/fertility (-0.748), dead in germ/hatchability of fertile eggs (-0.505) and dead in germ/hatchability of all eggs (-0.540). This study concluded that the Kashmiri RIR breed is an improved dual-purpose exotic breed which performs exceptionally well under intensive management systems in AJK, indicating its suitability for sustainable rural poultry production. The results provide a foundation for further genetic improvement programs and emphasize the importance of tailored management practices for optimizing productivity.